NagC represses N-acetyl-glucosamine utilization genes in Vibrio fischeri within the light organ of Euprymna scolopes - Sun, Yan; Verma, Subhash C.; Bogale, Haikel; Miyashiro, Tim (Frontiers in Microbiology, 2015)
Bacteria often use transcription factors to regulate the expression of metabolic genes in accordance to available nutrients. NagC is a repressor conserved among γ-proteobacteria that regulates expression of enzymes involved in the metabolism of N-acetyl-glucosamine (GlcNAc). The polymeric form of GlcNAc, known as chitin, has been shown to play roles in chemotactic signaling and nutrition within the light organ symbiosis established between the marine bacterium Vibrio fischeri and the Hawaiian squid Euprymna scolopes. Here, we investigate the impact of NagC regulation on the physiology of V. fischeri. We find that NagC repression contributes to the fitness of V. fischeri in the absence of GlcNAc. In addition, the inability to de-repress expression of NagC-regulated genes reduces the fitness of V. fischeri in the presence of GlcNAc. We find that chemotaxis towards GlcNAc or chitobiose, a dimeric form of GlcNAc, is independent of NagC regulation. Finally, we show that NagC represses gene expression during the early stages of symbiosis. Our data suggest that the ability to regulate gene expression with NagC contributes to the overall fitness of V. fischeri in environments that vary in levels of GlcNAc. Furthermore, our finding that NagC represses gene expression within the squid light organ during an early stage of symbiosis supports the notion that the ability of the squid to provide a source of GlcNAc emerges later in host development.